Can serum NGAL levels be used as an inflammation marker on hemodialysis patients with permanent catheter? - Yigit, Irem Pembegul; Celiker, Huseyin; Dogukan, Ayhan; Ilhan, Necip; Gurel, Ali; Ulu, Ramazan; Aygen, Bilge (Taylor & Francis Ltd, 2015)
Background: Neutrophil gelatinase-associated lipocalin (NGAL) is a member of lipocalin family and released from many tissues and cells. We aimed to investigate the relationship among serum NGAL levels, the inflammation markers (IL-6, hs-CRP, TNF-alpha) and different vascular access types used in dialysis patients. Methods: The study population included 90 patients and 30 healthy age-matched controls. The patients were divided into three groups (I, II, III) and group IV included the controls. In group I and II, the patients were with central venous permanent catheter and arterio-venous fistula, respectively. Group III included 30 patients with chronic renal failure. Hemogram, biochemical assays, ferritin, IL-6, hs-CRP, TNF-alpha, and NGAL were evaluated in all groups. Results: Serum NGAL levels were markedly higher in group I than in group II (7645.80 +/- 924.61 vs. 4131.20 +/- 609.87 pg/mL; p < 0.05). Positive correlation was detected between NGAL levels and duration of catheter (r: 0.903, p: 0.000), hs-CRP (r: 0.796, p: 0.000), IL-6 (r: 0.687, p: 0.000), TNF-alpha (r: 0.568, p: 0.000) levels and ferritin (r: 0.318, p: 0.001), whereas NGAL levels were negatively correlated with serum albumin levels (r: -0.494, p: 0.000). In multiple regression analysis, duration of catheter hs-CRP and TNF-alpha were predictors of NGAL in hemodialysis patients. Conclusion: Inflammation was observed in hemodialysis patients and increases with catheter. Our findings show that a strong relationship among serum NGAL levels, duration of catheter, hs-CRP and TNF-alpha. NGAL may be used as a new inflammation marker in hemodialysis patients.
Keywords: Central venous permanent catheter; hemodialysis; interleukin-6; neutrophil gelatinase-associated lipocalin; tumor necrosis factor-alpha